"My dirty little habit": Patient constructions of antidepressant use and the 'crisis' of legitimacy. (December 2015) - Ridge, Damien; Kokanovic, Renata; Broom, Alex; Kirkpatrick, Susan; Anderson, Claire; Tanner, Claire
Abstract: Discontents surrounding depression are many, and include concerns about a creeping appropriation of everyday kinds of misery; divergent opinions on the diagnostic category(ies); and debates about causes and appropriate treatments. The somewhat mixed fortunes of antidepressants – including concerns about their efficacy, overuse and impacts on personhood – have contributed to a moral ambivalence around antidepressant use for people with mental health issues. Given this, we set out to critically examine how antidepressant users engage in the moral underpinnings of their use, especially how they ascribe legitimacy (or otherwise) to this usage. Using a modified constant comparative approach, we analyzed 107 narrative interviews (32 in UKa, 36 in UKb, 39 in Australia) collected in three research studies of experiences of depression in the UK (2003–4 UKa, and 2012 UKb) and in Australia (2010–11). We contend that with the precariousness of the legitimacy of the pharmaceutical treatment of depression, participants embark on their own legitimization work, often alone and while distressed. We posit that here, individuals with depression may be particularly susceptible to moral uncertainty about their illness and pharmaceutical interventions, including concerns about shameful antidepressant use and deviance (e.g. conceiving medication as pseudo-illicit). We conclude that while people's experiences of antidepressants (including successful treatments) involve challenges to illegitimacy narratives, it is difficult for participants to escape the influence of underlying moral concerns, and the legitimacy quandary powerfully shapes antidepressant use. Highlights: Participant accounts pointed to depression and antidepressant legitimacy concerns. Moral uncertainty and distress means patients struggle to decode legitimacy/illegitimacy. Antidepressant counter-stories (e.g. increased authenticity) challenge illegitimacy. The legitimacy quandary powerfully shapes antidepressant interpretations and use. Patients might more pragmatically manage antidepressants via our study findings.